Impact of Allogeneic Hematopoietic Stem Cell Transplantation on Nutritional Status and Intake in Children. Issue 5 (19th August 2022) - Kvammen, Janne Anita; Thomassen, Rut Anne; Buechner, Jochen; Sitsabesan, Ajiitha; Bentsen, Beint Sigmund; Bechensteen, Anne Grete; Henriksen, Christine
Abstract : Objectives: This study aimed to describe the impact of allogeneic/haploidentical hematopoietic stem cell transplantation on nutritional status and intake in a group of children aged 2 to 18 years. Methods: In an observational study, data were collected prospectively. Patients were prescribed individual nutritional support by hospital routines. Anthropometrics were measured pre-transplant at hospital admission and weekly from the day of transplant (day 0) until day +28. z scores for weight, height, and BMI were calculated using Norwegian growth references to assess nutritional status. Pre-transplant diet was assessed on the day of hospitalization. Nutrient provision from enteral nutrition (EN = oral and tube) and parenteral nutrition (PN) was assessed by daily records from day +1 until day +28, or previous discharge, and compared with recommendations (RI) from the Nordic Nutrition Recommendations and ESPGHAN guidelines. Total energy intake was presented as the percentage (%) of basal metabolic rate (BMR) calculated by the Schofield equation. Macro- and micronutrient provisions were presented as medians (interquartile range) and the % of RI. Results: Twenty-eight patients, mean age 10.3 years (range 3.5–16.6), were included. Two-thirds (n = 18) had malignant diseases. At admission, mean weight Z-score was −0.3, height z scores −0.7, and BMI Z-score 0.1. Eighteen percent (n = 5) were stunted and 25% (n = 7) had overweight. At admission, 25% (n = 7) had established tube feeding, and 7% (n = 2) also had PN. No significant changes in weight z scores were detected during the studied weeks ( P = 0.454). The median daily energy provision was 115% (110–123) of BMR and proteins 1.5 (1.3–1.8) g/kg. EN was provided during a median of 93% of the studied days and provided 21% of the energy. PN was given on a median of 96% of the studied days and provided 79% of energy. RI for vitamins, magnesium, and zinc was met. Provision of copper, iodine, selenium, calcium, and phosphate was below RI. Conclusions: Combined EN and PN providing 115% of BMR and 1.5 g/kg protein ensured stable weight by day +28 and covered RI, except for trace elements and minerals.